Розвиток етнографії в Наддніпрянській Україні наприкінці XIX – на початку XX століття (історіографічний аспект) - Микитчук, С. (Народна творчість та етнографія, 2009)
The researcher elucidates in detail the development of the Ukrainian ethnography (in a historiographical aspect) using the examples of the prominent personalities with their guiding works in this field. He makes a conclusion about the most important achievement of the ethnographers of a period ca. 1900s – the transition from the descriptive approach to the historically comparative method in the Ukrainian ethnography.